2019
DOI: 10.1016/j.renene.2019.01.077
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional analysis of groundwater pumping for irrigation purposes: Economic, energy and environmental characterization for PV power plant integration

Abstract: Nowadays, the agriculture sector presents relevant opportunities to integrate renewable energy sources as an alternative solution to mitigate fossil-fuel dependence and decrease emissions. Moreover, this sector demands a detailed review of energy uses and other factors that are addressed as priority issues in most developed countries. In this framework, groundwater pumping energy requirements for agriculture irrigation emerge as a relevant topic to be improved in terms of power demand. Actually, this demand is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…These systems are then characterized through a multidimensional criteria scenario to consider energy, economic, and environmental aspects. This characterization is in line with recent approaches addressed by the authors to discuss the application of renewables for underground water resource purposes [40]. From this preliminary characterization in a multidimensional framework, an MCDM approach is used to provide a classification of groundwater pumping systems, with the aim of making the identification of optimal solutions easier.…”
Section: Overall Processmentioning
confidence: 54%
“…These systems are then characterized through a multidimensional criteria scenario to consider energy, economic, and environmental aspects. This characterization is in line with recent approaches addressed by the authors to discuss the application of renewables for underground water resource purposes [40]. From this preliminary characterization in a multidimensional framework, an MCDM approach is used to provide a classification of groundwater pumping systems, with the aim of making the identification of optimal solutions easier.…”
Section: Overall Processmentioning
confidence: 54%
“…A more detailed economic analysis, including investments, should be conducted to estimate the best solution. A recent detailed economic analysis carried out by the authors can be found in [59].…”
Section: Pv Installations Connected To the Grid: Surplus Of Annual Enmentioning
confidence: 99%
“…One of the most commons application of PV systems in the development countries is water pumping, which promotes social and economic development (KORDZADEH, 2010), mainly in isolated rural areas to cover human needs (RUBIO-ALIAGA et al, 2019). Such pumping application can be directed to irrigation in rural areas (SONTAKE; KALAMKAR, 2016), especially for family farmers not served by public services.…”
Section: Introductionmentioning
confidence: 99%
“…Such pumping application can be directed to irrigation in rural areas (SONTAKE; KALAMKAR, 2016), especially for family farmers not served by public services. Furthermore, irrigation is a major user of power and during recent decades has progressively required greater amounts of energy (RUBIO-ALIAGA et al, 2019). Besides costs reduction, innovations in renewable energy turns solar PV pumping irrigation a feasible technology to the progress (GAO et al, 2018).…”
Section: Introductionmentioning
confidence: 99%